Exploring the Relationship Between Longitudinal Course-Taking Patterns and In-State Transfer Into STEM Fields of Study. (4th March 2019) - Wang, Xueli; Lee, Yen; Wickersham, Kelly
ABSTRACT: Community colleges have increasingly played a critical role in expanding the pathway to baccalaureate degrees in science, technology, engineering, and mathematics (STEM) fields of study. At the same time, little is known about the course pathways that facilitate transfer into STEM disciplines at 4-year institutions. Adopting the STEM momentum concept, this research explored course-taking patterns that predict transfer into STEM fields of study and the timing of transfer. Employing a combination of longitudinal multidimensional k-means cluster analysis and multinomial logistic regression, the study revealed five clusters of course-taking patterns. Among them, three clusters of course-taking exhibited momentum toward transfer in STEM: one concentrating on courses in general education, one centering around major-specific coursework within and outside of STEM, and one involving the coupling of remedial courses and a broad distribution of courses within and beyond STEM. Furthermore, the first two patterns seemed to generate optimal momentum for middle transfer compared with early or late transfer, whereas the third cluster exhibited momentum for middle transfer and even greater momentum for late transfer. Discussion of the findings in the context of STEM momentum and implications for policy, practice, and research are presented.